Urbanization‐induced regional warming in Yangtze River Delta: potential role of anthropogenic heat release - Xiaomei Wang; Xuguang Sun; Jianping Tang; Xiuqun Yang (International Journal of Climatology, 2015)
Accompanying with the rapid urbanization in Yangtze River Delta ( YRD ), large amounts of anthropogenic heat are released into the atmosphere, which is becoming a more and more severe issue for the local climate. To understand what role anthropogenic heat release ( AHR ) plays in the urbanization‐induced regional warming, high‐resolution (3 km) Weather Research and Forecast WRF model experiments are carried out for 7 years (2001–2007) with different configurations of urban land use (ULU) and AHR . The results show that AHR can cause notable warming in almost the whole YRD rather than confining to the local cities where it releases, which is more significant in winter than in summer if the same amounts of AHR apply, especially at winter night. And furthermore, it can decrease (somewhat increase) the diurnal temperature range ( DTR ) in winter (summer). On the contrary, urban canopy effect due to the change from rural to ULU can produce a stronger warming in summer than in winter, and always reduce DTR in both winter and summer. Contribution of AHR to the sensible heat flux in urban regions is responsible for those AHR ‐caused warming and DTR features, because it is larger in winter and at winter night but much smaller in summer and at summer night. Without ambient wind effect, AHR ‐caused warming centres in cities and spreads around homogeneously. However, under the prevailing wind, it has less magnitude, shifts to the downwind city edges and forms a warming belt along the wind direction, which may favour linking the adjacent AHR ‐caused warming together. On the other hand, AHR ‐caused warming depends on the city sizes that are proportional to the total amount of AHR emitted.